Learning Medium to Improve Science Literacy - Listianingsih Listianingsih; Aditya Rheina Anggraeni; Lilis Kurniawati; Dian Ashari; M. Dede Hermawan; Supardi U.S Supardi U.S; Huri Suhendri (MASI Mandiri Edukasi, 2026)
Indonesian students continue to demonstrate weak scientific literacy, as indicated by international assessment results, underscoring the need for more effective, contextually relevant learning innovations. This study aims to analyze the implementation of ZEP Quiz in science instruction and to examine its contribution to improving students’ scientific literacy in a madrasah context. The research applied a qualitative case study approach involving eighth-grade students and a science teacher at MTsN 23 Jakarta. Data were obtained through classroom observations, semi-structured interviews, questionnaires, and document analysis, and were analyzed using the interactive model of Miles and Huberman. The results indicate a significant improvement in student learning achievement, with the mean score increasing from 44 in the pretest to 80 in the posttest, and 96.6% of students showing positive progress. Qualitative findings reveal that ZEP Quiz use strengthens student engagement, learning motivation, and scientific literacy competencies, particularly in explaining scientific phenomena, interpreting data, and applying concepts to real-world contexts. These findings confirm that ZEP Quiz is an effective digital learning medium for enhancing scientific literacy through active and student-centered science learning in a madrasah environment.